Acremonium implicatum, a seed-transmitted endophytic fungus in Brachiaria grasses - Dongyi, H.; Kelemu, Segenet (Scientific Societies, 2004)
The pan-tropical grass genus Brachiaria comprises about 100 species, several of which are forages of economic importance, particularly in tropical America. Acremonium implicatum is a fungus that forms an endophytic association with at least some of these economically important grasses. To ascertain whether A. implicatum can be seed transmitted in Brachiaria species, we vegetatively propagated, under greenhouse conditions, 20 tillers from an endophyte-infected mother plant obtained from each of 14 Brachiaria hybrids and species. Ten tillers of each genotype were treated with the fungicide tebuconazole to eliminate the endophyte, and the other 10 were left untreated. Seeds were then harvested individually from all 20 of these genetically identical plants, germinated, and the seedlings grown. A previously developed polymerase chain reaction-based method used a pair of endophyte-specific primers to amplify a diagnostic 500-bp DNA fragment. The seedlings generated from seeds harvested from endophyte-infected plants also tested positive, whereas those from seeds of endophyte-free plants showed no amplification products. This is the first report of A. implicatum being transmitted through seeds of Brachiaria grasses.